Targeting Household Deprivations for Multidimensional Poverty Alleviation: An Application to Tunisian Data - Khaled Nasri; Adnen Weslati (Global Labor Organization (GLO), 2022)
This paper proposes a targeting methodology focused on household's deprivations that helps the public decision-maker in Tunisia to alleviate multidimensional poverty. In the first part of this research, we intend to decipher the relationship between official poverty measurement and anti-poverty programs currently implemented in Tunisia, with special emphasis on their targeting performance and on the divergence observed between the beneficiary selection process at the regional level and the official identification of poor households. Next, we will outline the proposed targeting methodology using the counting identification approach and we estimate three groups of potential beneficiaries reflecting three degrees of poverty. Our empirical findings show that if a household becomes deprived in one dimension, then he will automatically be considered a potential beneficiary of the anti-poverty program. In terms of budget allocation, categorizing beneficiaries by group allows the public decision-maker to prioritize the most urgent situations in the country, even in the case of an austerity policy. On the other hand, to eradicate poverty in all its forms everywhere, it would be useful to strengthen the targeting of the poor population through a forward-looking policy targeting households living in vulnerability to poverty.
Keywords: C54; C43; I18; H12; 330; Multidimensional Poverty Alleviation; Targeting; Counting Approach; Tunisia